2009
DOI: 10.3109/02699200903242970
|View full text |Cite
|
Sign up to set email alerts
|

Lexical-semantic immaturities manifesting as grammatical disorders: Evidence from a child language sample

Abstract: Given the growing evidence of the integral role that semantic development plays in normal child syntactic acquisition, it is very likely that lexical-semantic deficits can have ramifications for a child's grammar. This paper illustrates how semantics and syntax interact in a case study of a child, 5;3 years, with apparent grammatical deficits. Using concepts from Principles and Parameters Theory, a language sample analysis revealed that what appeared to be purely grammatical deficits arose via underlying lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Words provide the foundation for human thought (Sapir, ; Waxman & Leddon, ; Whorf, ). These fundamental linguistic units are essential for conveying communicative intent, establishing categorical concepts (Booth & Waxman, ; Fulkerson & Waxman, ), acquiring the syntax of one's native language (Gillette, Gleitman, Gleitman, & Lederer, ; Mok & Kipka, ), developing early literacy skills (Spencer, Kaschak, Jones, & Lonigan, ), and participating in social routines. For many parents, the production of their child's first word is cause for celebration.…”
Section: Introductionmentioning
confidence: 99%
“…Words provide the foundation for human thought (Sapir, ; Waxman & Leddon, ; Whorf, ). These fundamental linguistic units are essential for conveying communicative intent, establishing categorical concepts (Booth & Waxman, ; Fulkerson & Waxman, ), acquiring the syntax of one's native language (Gillette, Gleitman, Gleitman, & Lederer, ; Mok & Kipka, ), developing early literacy skills (Spencer, Kaschak, Jones, & Lonigan, ), and participating in social routines. For many parents, the production of their child's first word is cause for celebration.…”
Section: Introductionmentioning
confidence: 99%
“…Potential usage of the database in investigating the form-content interface in language acquisition of young children According to Bloom (1991), young children acquire syntax and semantics together to lay the foundations of early expressions, and these two domains interact in a bidirectional manner to regulate the acquisition in early child language (Mok and Kipka, 2009). As mentioned, a certain form can be used to express various semantic content categories while an individual semantic content category can also be expressed with different forms.…”
Section: Acquisition Of Semantic Content Categories and The Underlyin...mentioning
confidence: 99%
“…It was suggested that they first acquire the syntax of simple sentences to express a core of simple meanings, and subsequently the syntax of complex sentences in order to express the relational meanings between different propositions conveyed by the simple sentences. More recently, a growing body of literature on the integral role of semantic knowledge in child syntax acquisition has also been reported (Pérez-Leroux et al, 2008;Mok and Kipka, 2009). Given the importance mentioned above, it will be invaluable to examine the role of semantic content in the acquisition of early expressions in children.…”
Section: Introductionmentioning
confidence: 99%